Effect of sweet chestnut extract (Farmatan®) on the digestibility and bioavailability of nitrogen and some minerals in the laboratory rats - Tatjana PIRMAN; Andrej OREŠNIK (Acta Agriculturae Slovenica, 2016)
Study was conducted to investigate the dietary effect of hydrolysable tannin from sweet chestnut on the protein digestibility and bioavailability, dry matter and organic matter apparent digestibility and apparent digestibility and apparent bioavailability of some mineral elements. Ten male Wistar rats (98.9 g ± 25.6 g of body mass) were fed ad libitum with balanced diets. In the experimental diet 0.1 % of sweet chestnut extract (SCE) was added to the diet. Five days balance experiment takes place after fifteen days of adaptive period. SCE did not have any influence on the protein quality measurements or dry matter and organic matter apparent digestibility. Tannin significantly (p < 0.05) decreased the digestibility and bioavailability of Ca and Fe. The digestibility of Na was unchanged (97.76 % and 97.31 % in control and SCE group, respectively), but bioavailability significantly decreased in SCE group (53.16 %) as compared to the control group (74.17 %). On the contrary, the apparent digestibility of Se significantly increased, (64.25 %) in SCE group compared to the control group (52.31 %).